2022
DOI: 10.3390/foods11131944
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Selected Psychological Factors in Healthy-Sustainable Food Consumption Behaviors during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic and the consequent precautions and dispositions adopted have triggered substantial changes in daily health-related behaviors, including food consumption habits. The psychological impact of the pandemic has been considered one of the factors affecting this transition and requiring consideration when targeting healthy-sustainable behavior preservation. The present study describes the results of a survey conducted on a convenience sample of Italian residents (n = 2272) during the first phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The scientific literature has explored the relationships between dietary patterns, their drivers of choice, and pro-environmental behavior, such as an increase in fruit and vegetable consumption and a decrease in meat intake [21][22][23]. Many studies have analyzed dietary choices in relation to personal factors such as instruction level [24][25][26], personal psychological factors [26][27][28], personal motivations, attitudes, health concerns [29][30][31], the availability of healthy food [32], and exposure to news and advertising related to food consumption [33]. Among the individual factors, mindfulness, considered as the ability to live in the present moment without judging the situation, seems to be relevant to the definition of dietary choices [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature has explored the relationships between dietary patterns, their drivers of choice, and pro-environmental behavior, such as an increase in fruit and vegetable consumption and a decrease in meat intake [21][22][23]. Many studies have analyzed dietary choices in relation to personal factors such as instruction level [24][25][26], personal psychological factors [26][27][28], personal motivations, attitudes, health concerns [29][30][31], the availability of healthy food [32], and exposure to news and advertising related to food consumption [33]. Among the individual factors, mindfulness, considered as the ability to live in the present moment without judging the situation, seems to be relevant to the definition of dietary choices [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic caused lifestyle changes such as less physical activity, social isolation, and disrupted sleep patterns, which affected dietary habits and led to a decline in mental health ( Caroppo et al, 2021 ). A study found a correlation between healthier-sustainable food consumption and lower anxiety, depression, and stress symptoms ( Zanatta et al, 2022 ). Moderate-intensity physical activity, including walking, jogging, and house cleaning, may also be beneficial ( Marconcin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of some studies indicate that the pandemic could have impacted sustainable food consumption negatively. Zanatta et al (2022) claim that among the respondents who took part in the study, the biggest part did not change their eating habits during the coronavirus, and among those who did, there were both positive and negative cases in sustainable food consumption.…”
Section: Sustainable Consumer Behaviourmentioning
confidence: 99%